An Analysis of Teacher’s In Teaching Reading Comprehension Using Scaffolding, Think Aloud, and Reciprocal Strategies at the Grade X Students - Rohima Nur Aziza Al Hakim; Irwana Fitri (Arus Jurnal Pendidikan, 2022)
This study aims at finding the teacher strategies in teaching reading comprehension and how those strategies implemented in teaching reading comprehension at the tenth grader of SMAN 04 Bombana. The design of the research used descriptive qualitative method. The subject of this research was the English teacher of ten grade at SMAN 04 Bombana. Based on the findings the teacher’s strategy in teaching reading comprehension in the ten grade of SMAN 04 Bombana, are Scaffolding, Think-Aloud and Reciprocal Teaching. Scaffolding strategy was implemented by providing examples of reading with correct pronunciation. Then, the teacher implemented think-aloud by providing direction and asking students thought on their reading comprehension. While reciprocal was implemented to provide opportunities for students to be more active and independent in understanding reading text.